Pengaruh Model Direct Instruction terhadap Kemampuan Teknik Dasar Memainkan Alat Musik Hadrah pada Siswa Disabilitas Netra Kelas X - Dandi, Dandi; Prystiananta, Nostalgianti Citra; Mais, Asrorul (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study investigates the impact of the direct instruction model on the basic technical skills of playing the hadrah instrument among tenth-grade blind students at the Branjangan State Special Needs School in Jember. This study employed a quantitative experimental method with a